Fishery of threadfin breams with some aspects on the biology and stock assessment of Nemipterus mesoprion (Bleeker, 1853) off Malabar coast - Manojkumar, P P (Indian Journal of Fisheries, 2011)
The average annual catch of threadfin breams along the Malabar coast was 16,754 t during 1998-2005. The fishery was constituted by Nemipterus japonicus (46.8 %) and N. mesoprion (53.2 %). Peak landings were noticed during August- September. Studies on N. mesoprion revealed that there is no significant difference in the length weight relationship between sexes, and hence a common equation was fitted as Log W = -3.9620+2.8298 Log L. The asymptotic length (Lô€ƒ) and growth coefficient (K) were estimated as 299 mm and 0.79 y-1 respectively. N. mesoprion grows to 164, 238, 271 and 287 mm at the end of first, second, third and fourth years. The total mortality, fishing mortality and natural mortality were 4.93 y-1, 3.41 y-1 and 1.52 y-1 respectively. The length at first capture was 105.4 mm. The resource is over exploited, and hence there is a need for reducing the fishing pressure to sustain the fishery.